1997
DOI: 10.1046/j.1365-2648.1997.1997025123.x
|View full text |Cite
|
Sign up to set email alerts
|

The trait and process of resilience

Abstract: Resilience is the ability of people to 'spring back' in the face of adversity. It is an important concept for nurses as we endeavour to assist individuals to meet the challenges of living with illness and ageing. Researchers from many disciplines in both the social and health sciences have investigated resilience of individuals throughout the life cycle in a variety of situations related to health as well as other life events. Some researchers have investigated resilience as a trait of individuals while other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1
20

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(185 citation statements)
references
References 19 publications
(20 reference statements)
6
155
1
20
Order By: Relevance
“…Recent studies have also emphasized the importance of the psychological component as a factor that affects children’s resilience (Fu, 2012; Grotberg, 2001; Massad et al, 2009; Masten, 2014; Wang, Zhang, & Zimmerman, 2015). Other studies have identified psychological, emotional, cognitive, and mental components as individual and personality traits or characteristics (Jacelon, 1997; Wagnild & Young, 1993), which can determine the capacity of children in disasters, in line with the current study. These characteristics can also be used as indicators of children’s resilience.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recent studies have also emphasized the importance of the psychological component as a factor that affects children’s resilience (Fu, 2012; Grotberg, 2001; Massad et al, 2009; Masten, 2014; Wang, Zhang, & Zimmerman, 2015). Other studies have identified psychological, emotional, cognitive, and mental components as individual and personality traits or characteristics (Jacelon, 1997; Wagnild & Young, 1993), which can determine the capacity of children in disasters, in line with the current study. These characteristics can also be used as indicators of children’s resilience.…”
Section: Discussionsupporting
confidence: 82%
“…Resilience as a personal characteristic leads to positive adaptation and moderates the negative effects of stressors, enabling people to rehabilitate and maintain their health in spite of existing problems (Tonmyr, Wekerle, Zangeneh, & Fallon, 2011; Wagnild & Young, 1993). According to Zolkoski and Bullock (2012), studies conducted over the past four decades on the concept of resilience indicate that this is a challenging concept for researchers, and there are several different definitions of resilience (Jacelon, 1997; Leipold & Greve, 2009; Nourian, Mohammadi Shahbolaghi, Nourozi Tabrizi, Rassouli, & Biglarrian, 2016; Vinson, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that resilience as a baseline characteristic or trait may facilitate coping with cancer, but could also be an outcome of a successful adaptation to the 'trauma' of being diagnosed with and treated for cancer (Jacelon, 1997;Molina et al, 2014). As resilience is attended by positive emotional experiences and might be a more common reaction to traumatic experiences than generally believed (Bonanno, 2004), a decline in a persons' vulnerability to experience anxiety over the course of cancer treatment is logically consistent.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, emotional resilience has been used as a concept to imply the flexible use of emotional resources for adapting to adversity (Waugh, Fredrickson, & Taylor, 2008) or as the process linking resources (adaptive capacities) to outcomes (adaptation) (Norris, Stevens, Pfefferbaum, Wyche, & Pfefferbaum, 2008). Researchers using this concept view resilience as a process or force that drives a person to grow through adversity and disruption (Jacelon, 1997;Richardson & Waite, 2002;Richardson, 2002). The resilience may vary according to age (e.g.…”
Section: Current Conceptualisations Of Resiliencementioning
confidence: 99%